AN ANALYSIS OF CONVERSATIONAL IMPLICATURES DURING THE DEBATES BETWEEN 2012 CANDIDATES OF DKI JAKARTA GOVERNOR - Kusumah, Dony Wijaya (2015)
This study seeks to investigate the conversational implicatures during the debate between 2012 candidates of Jakarta Governor and to identify which maxims the candidates failed to observe, also to identify what implicatures that are attained from the violated maxims. Data were taken from DKI Jakarta governor candidates debate aired on Metro TV on August 18, 2012. Data relevant to implicatures were marked and numbered. The data were analyzed by classifying conversations with maxim violations. The results show that the governor candidates commit flouting towards Grice's (1975) maxims. The maxim the candidates violated the most was relevance maxim. Furthermore, the flouting occurs due to several factors comprising lack of knowledge, insufficient evidence, and avoidance answering questions in purpose. However, even though some violations were done, some of the candidates were able to use sentences or utterances in compliance with the cooperative principles since only half of the data that are violated. Keywords: Conversational Implicatures, Debate, Grice's Maxims, Maxims Flouting Abstrak: Penelitian ini bertujuan untuk mengetahui implikatur percakapan pada acara debat antara calon Gubernur Jakarta tahun 2012 dan untuk mengidentifikasi maksim-maksim apa saja yang di langgar, serta untuk mencari tahu apa makna implisit yang terkandung ketika pelanggaran maksim tersebut terjadi. Data di ambil dari debat para calon Gubernur DKI Jakarta 2012 yang ditayangkan di Metro TN pada tanggal 18 Agustus 2012. Data yang berhubungan dengan implikatur ditandai dan diberi nomor. Data kemudian di analisis dengan cara mengelompokan percakapan dengan jenis maksim yang dilanggar. Hasil penelitian menunjukan bahwa benar adanya para calon Gubernur DKI Jakarta 2012 melakukan pelanggaran terhada maksim Grice. Maksim yang paling sering dilanggar adalah maksim relevan. Hal ini disebabkan oleh beberapa faktor yang diantaranya adalah karena kurangnya pengetahuan, kurangnya bukti dalam menjawab, bahkan beberapa pelanggaran sengaja dilakukan demi menghindari menjawab pertanyaan Bagaimanapun, terlepas dari maksim yang dilanggar oleh para calon kandidat, para calon tetap sadar akan prinsip kerjasama dalam percakapan. Kata Kunci: Implikatur percakapan, Debat, Maksim Grice, Pelanggaran Maksim.